Liver Disorders : A Point of Care Clinical Guide - Saeian, Kia; Shaker, Reza (Springer International Publishing : Imprint: Springer, 2017)
This book is a comprehensive and easy-to-access guide not only in the diagnosis of the various types of liver disease but in the management of specific disorders, including the particular nuances of the care of the patient with liver disease. It provides a resource to the practitioner caring for patients with liver disease for addressing everyday questions posed by patients and their families, as well as referring physicians, in a manner that can easily be conveyed. The spectrum covered includes appropriate testing and disease monitoring of patients, use of medications, supplements, alternative therapies and alcohol, operative risk assessment, implementation of health maintenance for patients with chronic liver disease and cirrhosis, identification and management of particular complications of cirrhosis, and appropriate referral for liver transplantation, as well as management of special populations. Written by experts in the field, Liver Disorders: A Point of Care Clinical Guide is a valuable resource for clinicians who treat patients with a variety of liver disorders. .
Keywords: Medicine.; Gastroenterology.; Hepatology.; Surgical transplantation.; elektronické knihy; electronic books